A RELATIONSHIPS OF WOMEN AND NATURAL WITH KHAZANAH CULTURE AND HUMANITIES - Farid Aulia; Prinsi Rigitta (Jurnal Ekonomi, 2023)
Preservation of the natural environment is the main stream in every development activity carried out. Various parties maintain the natural environment so that it remains sustainable, starting from the government, campuses, non-governmental organizations, to environmentalists who campaign in various forms of culture and literature. This discussion is the aim of research on the role of women in protecting the natural environment so that it remains sustainable. The data to be collected comes from sourcestext of quotations or statements that refer to attitudes or statements containing ecological elements by female characters in literary works. The relationship between women and the natural environment is personified like an inanimate object, but not an object to be dominated and exploited. This condition encourages humans to interact with the natural environment and women always maintain harmony in egalitarian relationships. Literary works act as triggers to raise people's cultural awareness of various natural environmental issues that arise. In addition, literary works can be a reflection of social life. Various events that arise in life become a source of inspiration. The natural environment is the center for the birth of several poems, poems, short stories, novels.